2008
DOI: 10.1007/s10620-008-0372-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Recombinant Expression and Characterization of Human Augmenter of Liver Regeneration

Abstract: The rhALR is successfully expressed highly effectively with anticipated MW, N-terminal, and antigenicity. It could play an important role in relieving acute hepatic injury and hepatic failure by promoting hepatic cell proliferation and improving liver function in CCl(4)-intoxicated mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In our experiments, as other investigators, 4, 10, 12, 14, 15, 29 we used a small 15-kDa recombinant form of ALR that, mainly reported as an extracellular cytokine, 12, 26 represents the smallest yet functional protein capable of participating in the intracellular redox-dependent signalling pathways. 12 Indeed, the small 15-kDa ALR form, similarly to other ALR homologous proteins identified in all organisms from viruses to mammals, 6 maintains a well conserved amino-acid domain, CxxC, at the C-terminus part of the molecule, responsible for its sulfhydryl oxidase enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our experiments, as other investigators, 4, 10, 12, 14, 15, 29 we used a small 15-kDa recombinant form of ALR that, mainly reported as an extracellular cytokine, 12, 26 represents the smallest yet functional protein capable of participating in the intracellular redox-dependent signalling pathways. 12 Indeed, the small 15-kDa ALR form, similarly to other ALR homologous proteins identified in all organisms from viruses to mammals, 6 maintains a well conserved amino-acid domain, CxxC, at the C-terminus part of the molecule, responsible for its sulfhydryl oxidase enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…In line with other investigators, in the present experiments, we used a rALR form of 15 kDa, containing the well-conserved, biologically active, C-terminal domain of the molecule. 29, 30, 39 All the chemical reagents were purchased, if not specifically reported, from Sigma-Aldrich (Milan, Italy). The polyclonal antibody against ALR (MultiBind GmbH, Cologne, Germany; a gift from Dr. Thomas Lisowsky) has already been employed for specific identification of ALR.…”
Section: Methodsmentioning
confidence: 99%
“…18 Augmenter of liver regeneration (ALR) was purified from the liver of newborn rats and cloned by Hagiya et al 19 Several studies have found that ALR can stimulate hepatocyte proliferation and protect the liver from acute liver failure. [20][21][22] Recent studies have shown that depletion of ALR in hepatocytes by anti-sense oligonucleotide transfection induced hepatocyte apoptosis, while recombinant human ALR (rhALR) significantly decreased hepatocyte apoptosis in vitro. 23,24 The expression of exogenous ALR increased the survival of hepatoma cells, accompanied by a decrease in apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Erv1/ALR has been described to enhance the regenerative capacities of liver tissue [9597]. For this role of Erv1/ALR two different mechanisms were proposed.…”
Section: Physiological Impact Of Mia40 and Erv1/alrmentioning
confidence: 99%